The protective effect of social support on all-cause and cardio-cerebrovascular mortality among middle-aged and older adults in the US - Yu Wang; Jun-Jun Wang; Hao-Feng Zhou; Wei-Ya Li; Ying-Xue Liao; Ming-Yu Xu; Chuan-Yu Gao; Bo Lv (Scientific Reports, 2024)
Abstract The relationship between social support and mortality, especially cardio-cerebrovascular mortality, still has some limitations in the assessment of social support, sample selection bias, and short follow-up time. We used the data from 2005 to 2008 National Health and Nutrition Examination Survey to examine this relationship. The study analyzed a total of 6776 participants, divided into Group 1, Group 2, and Group 3 according to the social support score (0–1; 2–3; 4–5). Multivariable adjusted COX regression analyses of our study showed that Group 3 and Group 2 had a reduced risk of all-cause and cardio-cerebrovascular mortality (Group 3 vs 1, HR: 0.55, P < 0.001; HR: 0.4, P < 0.001; Group 2 vs 1, HR: 0.77, P = 0.017; HR: 0.58, P = 0.014) compared with Group 1. The same results were observed after excluding those who died in a relatively short time. Additionally, having more close friends, being married or living as married, and enough attending religious services were significantly related to a lower risk of mortality after adjustment. In brief, adequate social support is beneficial in reducing the risk of all-cause mortality and cardio-cerebrovascular mortality in middle-aged and older adults, especially in terms of attending religious services frequency, the number of close friends, and marital status.